2008
DOI: 10.1002/cncr.23934
|View full text |Cite
|
Sign up to set email alerts
|

Claudin 1 overexpression increases invasion and is associated with aggressive histological features in oral squamous cell carcinoma

Abstract: BACKGROUND.The authors have previously shown that overexpression of claudin 1 (CLDN1) is associated with advanced disease stage in oral squamous cell carcinomas (OSCCs). Their goal was to examine CLDN1 expression in a large series of primary OSCCs and to further investigate whether CLDN1 overexpression plays a role in invasion in OSCC.METHODS.CLDN1 gene expression levels were determined by quantitative real‐time reverse transcription polymerase chain reaction (QRT‐PCR) in 100 primary OSCCs. CLDN1 protein expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
60
4
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(71 citation statements)
references
References 38 publications
(45 reference statements)
5
60
4
2
Order By: Relevance
“…In addition, the disagreement may also be a result of the differences in the methods of detection and the types of antibodies used with varying cross-reactivity potential. Nonetheless, in conjunction with our finding, Dos Reis et al [33] found that the increased claudin-1 gene expression was associated with the increased angiolymphatic and perineural invasions, the prognostically relevant histopathologic features of OSCC [2].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In addition, the disagreement may also be a result of the differences in the methods of detection and the types of antibodies used with varying cross-reactivity potential. Nonetheless, in conjunction with our finding, Dos Reis et al [33] found that the increased claudin-1 gene expression was associated with the increased angiolymphatic and perineural invasions, the prognostically relevant histopathologic features of OSCC [2].…”
Section: Discussionsupporting
confidence: 90%
“…A handful of studies reported the altered claudin-1 expression in OSCC [25,31,33]. Compared to the normal oral mucosa, claudin-1 expression was altered in different grades of oral epithelial dysplasia and squamous cell carcinoma [26,31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OSCC has a high potential for local invasion and nodal metastasis and over 80% of early stage OSCC patients can be rescued by treatment, whereas less than 70% of advanced stage OSCC patients are incurable. The overall 5-year survival rates of OSCC have not improved significantly in the past 30 years, and it remains less than 50% [6][8]. Therefore, early detection and elucidation of the detailed molecular mechanism of OSCC are important.…”
Section: Introductionmentioning
confidence: 99%
“…130,131 Desmosomes are another cell-cell adhesion structure, which can suppress invasion. 132 However, overexpression of certain adhesion proteins, such as claudin 1 133 and desmoglein 3, 134 can enhance invasion. Although degradation of the ECM, especially the basement membrane, is a key property of invasive tumors, interaction with the ECM is also important for invasion and prognosis.…”
mentioning
confidence: 99%